Reformado de metano con CO2 sobre óxidos mixtos Ni-Mg-Al-Ce derivados de hidrotalcitas : Efecto de la relación Mg/Ni (2011)
ABSTRACT: Ni-Ce/Mg-Al catalysts were obtained by means of the hydrotalcite reconstruction method in the presence of [Ce(EDTA)]-complex. The effect of the Mg/Ni ratio was studied when the mixed oxide was reconstructed with 3 wt. % Ce loadings. The materials were characterized by X-Ray Diffraction (XRD), Thermal-Gravimetric Analysis (TGA), Temperature-Programmed Reduction (TPR-H2), Temperature-Programmed Oxidation (TPO) and CO2 Temperature-Programmed Desorption (TPD-CO2). The reduced catalysts were tested in CO2 reforming of methane under two operation regimens:i) reaction between 500 to 800ºC using volumetric ratios of CH4/CO2/Ar=5/5/40 and, ii) isothermal reaction at 700ºC using volumetric ratios of CH4/CO2=18/22 without diluent gas. The solids showed strong basiccharacteristics and high Ni-surface interactions which determined their catalytic performance. Catalysts with Mg/Ni molar ratios of 2 and 4 showed high CH4 and CO2 conversions with H2/CO molar ratios between 0.7 and 1.1 without coke formation under severe isothermal reaction conditions. The yields and activities were higher when reduction increased.